Skin autofluorescence as part of the comprehensive assessment of clinical and metabolic status of patients with end-stage chronic kidney disease - Darya Yu. Konovalova; Peter A. Lebedev; Olga V. Ushakova; Elena E. Potyakina; Dmitriy V. Kornilin; Vladimir N. Grishanov; Marina V. Komarova (КардиоСоматика)
BACKGROUND: Chronic kidney disease (CKD) is a common end-stage disease requiring kidney transplantation or dialysis, which main type is program hemodialysis (PHD). These high-cost technologies of renal replacement therapy have significantly improved over recent decades, but the quality of life remains low and mortality is still high, especially in patients receiving PHD. Currently, a number of parameters associated with poor prognosis have been identified, including skin autofluorescence (SAF), an affordable method to detect glycation end products (glycotoxins) in tissues, which claims to be an integral biomarker.